Lines, contours and legends: coordinates for vernacular mapping - Gerlach, J (SAGE Publications, 2014)
Harnessing the cartographic attributes of line, contour and legend, this paper generates a conceptual vocabulary attentive to the proliferation in everyday mapping. By developing theoretical work that questions the representational certitude of cartography, the paper argues that attention needs to be focused on the non-representational vectors of mapping. This is to establish the grounds for future empirical research into quotidian cartographies and their politics. Instead of categorizing these variegated, mapping practices as either ‘counter’ or ‘indigenous’ movements, the notion of ‘vernacular mapping’ is proposed as one way in which geographers might begin to encounter the vibrant micropolitics of contemporary cartography.